Qualitative Research Concepts: Phenomenology, Grounded Theory, Ethnography, Case Study, Narrative - Rio Luthfiandana; Lucy Lidiawati Santioso; Wenny Desty Febrian; Josua Panatap Soehaditama; Indra Sani (Siber Nusantara Research & Yayasan Sinergi Inovasi Bersama (SIBER), 2024)
Qualitative research concept articles: phenomenology, grounded theory, ethnography, case studies, and narratives are scientific literature articles within the scope of research methodology. The purpose of this writing is to build a hypothesis regarding the influence between variables which can later be used for further research within the scope of research methodology. The research method used is descriptive qualitative. Data was obtained from previous research that is relevant to this research and sourced from academic online media such as Publish or Perish, Google Scholar, digital reference books, and the journal Sinta. The results of this article are: 1) Phenomenology plays a related role to the concept of qualitative research; 2) Grounded theory is related to the concept of qualitative research; 3) Ethnography is related to the concept of qualitative research; 4) Case studies relate to the concept of qualitative research; and 5) Narrative relates to the concept of qualitative research.